A COMPARATIVE STUDY ON THE THERMAL PERFORMANCE OF MORTARS WITH DIFFERENT FORMULATIONS - Kabay, Nihat; Kizilkanat, Ahmet B. (YILDIZ TECHNICAL UNIV, 2020)
This paper comparatively analyze the mechanical and thermal performance of three different mortar mixes namely; ordinary Portland cement mortar, geopolymer mortar, and phase change material (PCM) incorporated geopolymer mortar. In geopolymer mortar ground pumice was used as the precursor material and combination of NaOH (Sodium hydroxide) and Na 2 SiO 3 (Sodium silicate) was used as the activator. In PCM modified mortar mix, sand was substituted by PCM by 25% by volume. Compressive strength and thermal performance of the mortar mixes were determined at 7 days on cubic and prismatic samples. Test results showed that the compressive strength is dramatically reduced in geopolymer mortar and further reduction was observed with PCM inclusion. Thermal performance of the geopolymer mortar and PCM modified mortar are improved with reduced density. PCM inclusion provided the best thermal insulation property by keeping the internal temperature of the test cubicle cooler and warmer during the heating and cooling cycles and furthermore delays the temperature increase or decrease in the internal space during the cycles.
Keywords: Phase change material; geopolymer; pumice; thermal performance; PHASE-CHANGE MATERIALS; CONCRETE; Engineering